Enzimas digestivas de esturión Acipenser gueldenstaedtii. Lipasas y Proteasas (revalorizacion de residuos) - Liebana, Clara (2025)
The circular economy in aquaculture involves integrating farming technologies, waste treatment and valorization strategies to optimize production, minimize environmental impact, and recycle valuable materials for sustainable development. From this perspective, this study aimed to process one of the most voluminous sturgeon Acipenser gueldenstaedtii processing waste, the viscera, to obtain and characterize digestive enzymes for potential biotechnological applications. Alkaline peptidases exhibited high stability for up to 120 min across a broad pH range (7–11) and at temperatures between 10 and 25 °C. Similarly, lipases remained highly stable over 120 min within a pH range of 7–10 and temperatures from 10 to 40 °C. Both enzymes retained activity at low temperatures and were fully denatured at 70 °C. In addition, peptidases showed strong stability in the presence of surfactants, salts—compounds commonly used in industrial processes—without loss of enzymatic activity. These results highlight the considerable potential of enzymes derived from sturgeon viscera for diverse biotechnological applications, supporting the advancement of circular economy strategies in the aquaculture sector.